Discussing issues of health promotion and research in the context of primary care during the ongoing austerity period: an exploratory analysis from two regions in Greece - Sbarouni, Vicky; Petelos, Elena; Kamekis, Apostolos; Tzagkarakis, Stylianos Ioannis; Symvoulakis, Emmanouil K.; Lionis, Christos (Medicine and Pharmacy Reports, 2019)
Background. In Greece, both Primary Health Care (PHC) system and National Health System (NHS) in general, were plagued by several inefficiencies even prior to the financial crisis; the imposed austerity measures dramatically worsened the level of health provision and access, especially for vulnerable social groups, resulting in an exacerbation of existing disparities and access gaps. Aim and methods. The current branch study was conducted in two regions of Greece, namely Crete and Epirus, with the main aim of eliciting responses to gather baseline information regarding crucial PHC-related aspects, using questionnaires with dichotomous questions. Directors or managers (physicians who have been assigned administrative/governance duties), of the Primary Health Care Centres (PHCCs) in two Greek geographic and administrative regions of Crete and Epirus, were invited to participate and to contribute to the investigation of issues on the provision of prevention and health promotion services, e-health topics and primary care research. Thirty directors/managers were approached and twenty-eight agreed to participate. Data processing and analysis of the responses was performed for the completed questionnaires. Results. Data analysis did not demonstrate a surprisingly substantial deviation in the average score of positive responses of directors/managers in the PHCCs of Crete in comparison to those of directors/managers in the PHCCs of Epirus. The findings show that several gaps exist in terms of prevention and health promotion resources and activities in both regions, while e-health, electronic health record (EHR) and telemedicine services are poorly developed. Conclusion. The study confirms that the Greek PHC is characterized by several inefficiencies, which may affect the quality of the services provided. An overall deficit has been emerged for PHCCs in both regions, a fact that indicates crucial points lacking in terms of overall PHC provision, thus adversely impacting upon living conditions, health quality and prevention.